The study of the lifting mechanism of the crane arm to a barge - Fratila, C.; Axinte, T.; Cojocaru, R. C.; Berescu, C.; Scurtu, I.C. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
During cargo loading and unloading, the vessels’ lifting gear, even if anchored or moored, is affected by the pitch and roll movements, in addition to the usual stresses, a similar shore crane is subjected to. This paper aims at presenting an analysis of the lifting operations of a boom crane pertaining to a self-propelled barge. The analysis starts with the meshing with triangle elements, the stresses and the embedding using the finite elements method. The crane and the pertaining boom were modeled using CAD design, NX 10.0 from Siemens. The lifting equipment of the ships boom crane may be subject to dangerous defects occurring during the loading and unloading process. Subsequently, the research emphasizes the stresses occurred in the piston rod and in the eye of the lifting equipment, using the finite element method (FEM). After the stress analysis, several fatigue matters are studied: fatigue safety factor, fatigue life, strength safety factor and crack. The damaging or breaking of the eye or of the piston rod from the lifting equipment of the ships boom crane is leading to the blocking of the cylinder with the result of unfavorable events, such as deformation of the boom crane, damaging the loads and even the danger of sinking the barge. The results of this analysis provide ship-owner and maintenance engineers a useful tool to take appropriate decision during inspection of the lifting gear of the ship, prior commencement of the loading and unloading operations.